Penetapan Kadar Sediaan Tablet Kombinasi Parasetamol Dan Tramadol Dengan Metode Spektrofotometri UV Lamda Berganda - Dimas Dwi Putra; Novena Yety L; C.E. Dhurhania (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
Paracetamol and tramadol can be combined as drug preparations to treat moderate to severe pain. Multiple UV lampda spectrophotometry method for assaying tablet preparations of a combination of paracetamol and tramadol can be used because both compounds have chromophore groups and provide maximum absorption in the UV spectrum. This study was conducted assays with the aim of providing information that the levels of paracetamol and tramadol in the combined tablet determined by the UV-lamda double spectrophotometry method can meet the levels requirements in the Indonesian Pharmacopoeia Edition VI Year 2020, not less than 90% and not more than 110% of the required levels. stated on the label.Design This research is a descriptive type of research. This research is conducted to determine the concentration of tablet preparations of a combination of paracetamol and tramadol with the multiple wavelength method. The wavelength used was 249 nm for paracetamol and 273 nm for tramadol.The results of the determination of the average concentration were 311,629 ± 0.965 mg/tablet with a recovery of 95,886% for paracetamol, while for tramadol 35,890 ± 4,344 mg/tablet with a recovery of 95,707% and resulted in a coefficient of variation of 0.310 % for paracetamol and 12.104% for tramadol. The levels of paracetamol and tramadol from the test results meet the requirements for the levels of active substances in medicinal preparations according to the Indonesian Pharmacopoeia Edition VI of 2020, which is not less than 90.0% and not more than 110% of what is stated on the label.